Proposals for a National Health Service - Great Britain. National Health Service
1946-01 1946 1940s 16 pages CONFIDENTIAL Proposals for a National Health Service [Note: Subject to a few modifications in detail, the proposals are applicable to Scotland as well as to England and Wales, and references to the Minister should be read in their application to Scotland as references to the Secretary of State.] Central Organisation 1. General responsibility for the service will rest on the Minister of Health. This will extend to mental, as well as physical, health services - the administrative functions of the Board of Control in mental health being absorbed by the Minister and the Board exercising only the quasi-judicial functions relating to the liberty of the subject under the lunacy and mental deficiency Acts. 2. The Minister will discharge his general responsibility through three main channels: - (1) For parts of the service best organised nationally - the hospital and specialist services - he will assume direct responsibility; but he will delegate the bulk of administration to new regional and local bodies, acting on his behalf and designed to give scope to people with local experience and knowledge to serve on them. (2) For parts of the service best organised locally - a wide variety of domiciliary and clinic services - direct responsibility will rest on local government, acting in its ordinary relationship with the Minister; this responsibility will be unified in the present major authorities, the county and county borough councils, or combinations of them, as "local health authorities." (3) For new family practitioner services - doctor and dentist - new local executive machinery will be set up, composed partly of members drawn from local authorities, partly of people selected by the Minister, partly of representatives of the doctors and others engaged in the service. These new local bodies will act within national regulations made by the Minister; and by the side of the /Minister 292/847/4/83